Saliva: A fluid in search of a diagnostic use - Jia Liu (Wolters Kluwer Medknow Publications, 2015)
Since saliva has been studied for more than 50 years and is relatively easy to collect, it is reasonable to ask why saliva is not in wider use as a diagnostic fluid. Here we discuss the criteria for diagnostic tests for diseases, barriers to use saliva for diagnostic testing, and the possibility of overcoming barriers to acceptance of saliva for diagnosis.